The Users’ Comments on Tiktok Account of Ishowspeed: A Study Morphological Errors Analysis - Suparwoto Sapto Wahono; Nadia Dwi Rahmawati; Sulistiana Khofifah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyse morphological errors found in the comment section of the TikTok account @iShowSpeed, focusing on inflectional, derivational, and compound morphology. Researchers used a qualitative descriptive approach. The data were collected through online observation on social media and document which were screenshot from social media. The data were collected using purposive sampling from users written comments on Tiktok account @iShowSpeed. The results showed that the most frequent errors were related to grammatical realization, which encompasses both syntactic and morphological issues. The most common issues were verb phrase errors, such as missing auxiliary verbs or incorrect tense usage (e.g.,